Spatial resolution of a laboratory based X-Ray cone-beam laminography scanning system for various trajectories. (April 2020) - Deyhle, Hans; Towsyfyan, Hossein; Biguri, Ander; Mavrogordato, Mark; Boardman, Richard; Blumensath, Thomas
Abstract: Computed laminography (CL), a long established NDT method, is ideal for the non-destructive evaluation of plate-like structures, for which conventional computed tomography (CT) is less well suited. This paper demonstrates the feasibility of implementing raster CL on a Nikon Metrology custom build X-ray CT scanner without the need for specialised equipment. To provide a more principled way to demonstrate the widespread adoption of CL for defect characterization in plate-like structures, a test specimen was designed and manufactured from Polyoxymethylene (Delrin) that allows well defined features of different size and orientation to be characterized. The study highlights the relation between direction-dependent spatial resolution, feature geometry and scan trajectory. It demonstrates that high-resolution and high-speed in situ volume-imaging of plate-like structures with large aspect ratios is viable at levels that would be challenging via CT or alternative three-dimensional NDT methods.